Politeness Strategies through Language Power and Style-Based Communication - Antonius Herujiyanto (Journal of Language and Literature, 2015)
It is reasonable to highlight that approving the use of intra-lingual and extra-lingual components means justifying the signs of ones politeness strategies to have appropriate communication. It would be rather different, however, when the scope is within the students writing skills. This paper focuses on the students implementation of those linguistic components as seen in their work assigned in Mass Media Communication (Journalism) class of the English Language Education Study Program of Sanata Dharma University, Yogyakarta. Not only does the discussion engage with the course objectives such as being able to make use of the language of news and the nature of investigative report, but it also involves the burning question of how politeness strategies portray such an appropriate application of the two linguistic components. Analysing the students work is, thus, an unavoidable method to use. This research paper is also grounded on the Indonesian indigenous wisdom sarujuk sithik-edhing [committing to win-win solution] of Katresnanism theory, contextualizing the students with the pro-active spirit of cultural pluralism as the nature of International journalism.